2023
DOI: 10.1007/s10775-023-09579-x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond job placement: careers for refugees

Abstract: In this article, we highlight the Australian country context to advocate for career support that extends beyond initial job placement in a segmented labor market to strengthen refugees’ skills and knowledge and future career development. We address systemic barriers while advocating for access to skilled career development practitioners, whose important expertise as members of multidisciplinary teams could enhance resettlement assistance. Strengthening the preparation of career development practitioners is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Recent STF-based research on immigrants and refugees, which was conducted using narrative instruments, identified perceived influences in terms of barriers and opportunities through a meaning-making process that emerged during interviews. Besides systemic barriers, such as language, limited access to local social capital, discrimination, stigma, and lack of recognition of prior qualifications and experiences [27][28][29], recent research underlines the role of other restrictive voices. Through the analysis of narratives of adult immigrants, these were traced as coming from the internal or the proximal context (i.e., family) [19].…”
Section: A Systems-theory-based Perspective On Migration Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…Recent STF-based research on immigrants and refugees, which was conducted using narrative instruments, identified perceived influences in terms of barriers and opportunities through a meaning-making process that emerged during interviews. Besides systemic barriers, such as language, limited access to local social capital, discrimination, stigma, and lack of recognition of prior qualifications and experiences [27][28][29], recent research underlines the role of other restrictive voices. Through the analysis of narratives of adult immigrants, these were traced as coming from the internal or the proximal context (i.e., family) [19].…”
Section: A Systems-theory-based Perspective On Migration Experiencementioning
confidence: 99%
“…This is the reason career support interventions are extremely important in constructing the active participation of immigrants in the host community. As underlined by the OECD [67], there is a need to support immigrants and refugees with quality career guidance and employment support [27]. This will provide them with support to move towards self-sufficiency, better well-being, transitional readjustment, and access to new opportunities.…”
Section: Conclusion Limits and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation